Sleep, health and society from aetiology to public health - Cappuccio, Francesco; Miller, Michelle A., Dr.; Lockley, Steven W. (Oxford : Oxford University Press, 2010)
This volume provides a preventive medicine approach to sleep medicine, looking at the epidemiological evidence that sleep deprivation and disturbance is linked to ill health, and exploring the public health implications with a view to developing preventive strategies.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Sleep -- Health aspects; Sleep deprivation